Guild Pricing in the Service Trades - Brown, William F.; Cassady, Ralph (Quarterly Journal of Economics, 1947)
The medieval guilds, 311. — Modern guild regulations in the service trades — the barbers: importance of legislative aid, 312; non-price regulations, 314; price-fixing laws, 316; enforcement of regulations, 323. — Economic aspects of the pricing of barber services: characteristics of the “product” and the market, 325; pricing without restriction on individual action, 328; pricing with concert of action but without benefit of legislation, 330; pricing with minimum price legislation but without extralegal concert of action, 331; pricing with minimum price legislation undergirding extralegal concert of action, 333. — Guild pricing in other trades, 335.